2015
DOI: 10.2217/fmb.15.48
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Aeruginosa : Arsenal of Resistance Mechanisms, Decades of Changing Resistance Profiles, and Future Antimicrobial Therapies

Abstract: Antimicrobial resistance is one of the most serious public health issues facing humans since the discovery of antimicrobial agents. The frequent, prolonged, and uncontrolled use of antimicrobial agents are major factors in the emergence of antimicrobial-resistant bacterial strains, including multidrug-resistant variants. Pseudomonas aeruginosa is a leading cause of nosocomial infections. The abundant data on the increased resistance to antipseudomonal agents support the need for global action. There is a pauci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
99
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 203 publications
(216 reference statements)
1
99
2
9
Order By: Relevance
“…1 24 anti biotics (El Zowalaty et al, 2015). The literature is rich in surveillance studies from all over the world reporting varying resistance rates among P. aeruginosa against different antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 24 anti biotics (El Zowalaty et al, 2015). The literature is rich in surveillance studies from all over the world reporting varying resistance rates among P. aeruginosa against different antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical variations and differences in the resistance rates of P. aeruginosa usually correlate with the prescription patterns of antimicrobial agents prescribing habits, overuse of antimicrobial agents in different parts of the world, and the selective pressure of certain 1 24 anti biotics (El Zowalaty et al, 2015). The literature is rich in surveillance studies from all over the world reporting varying resistance rates among P. aeruginosa against different antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the differences in the resistance rates of P. aeruginosa usually correlate with the prescription patterns of antibiotics by physicians, overuse of antibiotics, and the selective pressure of certain antibiotics. 11 Recent, studies showed that susceptibility of P. aeruginosa to currently used anti-pseudomonal agents, including ß-lactams, aminoglycosides, and fluoro-quinolones is decreasing. 12 Since resistance of P. aeruginosa to carbapenems, piperacillin, and other highly active antibiotics has emerged and is increasing, it makes treatment of P. aeruginosa infections troublesome.…”
mentioning
confidence: 99%
“…2 Resistensi antimikrob merupakan salah satu masalah kesehatan masyarakat yang dihadapi manusia sejak era ditemukan antimikrob. 3 P. aeruginosa merupakan salah satu bakteri yang memiliki semua mekanisme resistensi yang diketahui.…”
Section: Pendahuluanunclassified
“…Angka resistensi ini sangat bervariasi secara geografis, dilaporkan rendah di beberapa negara, namun sangat tinggi di beberapa negara lain. 3 Laporan angka resistensi P. aeruginosa termasuk prevalensi multidrug resistant P. aeruginosa (MDR P.a eruginosa), di Indonesia khususnya di Pekanbaru sangat terbatas.…”
Section: Pendahuluanunclassified